Estratégias de ensino da leitura no ensino fundamental: caminhos para a compreensão textual - Medeiros, Janaíne Freitas de (2020)
This research was motivated by concerns and questions about the teaching practices of reading and reading comprehension in Portuguese Language classes, in which it is observed the difficulty of students in the final years of Elementary School to go beyond the level of linguistic decoding. This reality has repercussions, above all, in the national exams that assess the reading performance of these students. Like the Basic Education Assessment System (SAEB), which has shown a low reading proficiency rate on the part of the students. With this, this research aims to contribute to the expansion of the reading competence of students of the 9th grade of Elementary School, in the city of Cabedelo-PB, from the teaching of reading strategies. The theoretical contribution of Leffa (1996), Solé (1998), Menegassi (2010), Feltes (2008), among other authors who conceive of reading in a socio-cognitive perspective, is the theoretical support. It is a qualitative and quantitative research, of a descriptive nature and of an applied nature. It is also characterized as research-action, since the researcher and participants work cooperatively. The research was applied in a 9th grade class, composed by 20 students, who participated in the action plan developed in three stages: (a) application of the Initial Diagnostic Assessment; ((b) development of the Pedagogical Intervention Plan, and (c) application of the Final Diagnostic Assessment.The diagnostic assessments were carried out based on objective questions related to the descriptors D-17 - Recognize the effect of meaning resulting from the use of punctuation and other notations - and D-18 - Recognize the effect of meaning resulting from the choice of a certain word or expression - of Topic V - Relationships between expressive resources and effects of meaning - of the SAEB.The results obtained revealed significant advances in student skills in relation to the mentioned descriptors D-17 and D-18, so that students started to evaluate and monitor their reading process. This highlights the need for the school, in addition to encouraging the habit of reading, to teach reading strategies that lead students to acquire proficiency in reading.